Importance of Women in Decision Making at Family Level in Patna Metropolitan City - Pandey, Purnima; Rai, Gayatri (National Geographical Journal of India, 2022)
The study is undertaken to analyze the importance of women's in decision making at family level in Patna City (Bihar, India) regarding the freedom of movement, family matters, to purchase home assets and family planning etc. This study examines the factors (particularly the independent variables) that might affect women's decision making power at the household level. The Women decision making index (WDMI) has been determined to ascertain the women's socio-economic status.In the present work two types of data such as Primary and Secondary both data have been used.The study reveals that most of the women (50%) are found to have equal status in the family with regard to taking various decisions. Along with, some background socio- economic characteristics such as women's educational levels and employment status appeared as an important factor, contributing to women's empowerment